2020
DOI: 10.3389/fonc.2020.609601
|View full text |Cite
|
Sign up to set email alerts
|

Identify and Validate the Transcriptomic, Functional Network, and Predictive Validity of FBXL19-AS1 in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common neoplastic diseases worldwide. Available biomarkers are not sensitive enough for the diagnosis of HCC, hence seeking new biomarkers of HCC is urgent and challenging. The purpose of this study was to investigate the role of F-box and leucine-rich repeat protein 19-antisense RNA 1 (FBXL19-AS1) through a functional network and inquire into its diagnostic and prognostic value in HCC. A comprehensive strategy of genomic data mining, bioinformatics and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Furthermore, another study revealed a positive correlation between FBXL19-AS1 TNM stage and poor prognosis of HCC patients, where FBXL19-AS1 acts as a regulation agent, controlling HCC-associated pathways, including cell cycle, microRNAs in cancer, viral carcinogenesis via ceRNA network [ 43 ]. Consequently, this lncRNA may be considered a diagnostic and prognostic biomarker [ 44 ]. Furthermore, a study demonstrated that lncRNA FBXL19-AS1 has a diagnostic biomarker potential and is considered an appropriate candidate as a prognosis biomarker in HCC [ 45 ].…”
Section: The Effect Of Fbxl19-as1 On Several Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, another study revealed a positive correlation between FBXL19-AS1 TNM stage and poor prognosis of HCC patients, where FBXL19-AS1 acts as a regulation agent, controlling HCC-associated pathways, including cell cycle, microRNAs in cancer, viral carcinogenesis via ceRNA network [ 43 ]. Consequently, this lncRNA may be considered a diagnostic and prognostic biomarker [ 44 ]. Furthermore, a study demonstrated that lncRNA FBXL19-AS1 has a diagnostic biomarker potential and is considered an appropriate candidate as a prognosis biomarker in HCC [ 45 ].…”
Section: The Effect Of Fbxl19-as1 On Several Cancersmentioning
confidence: 99%
“…Many studies have revealed that FBXL19-AS1 can regulate the expression of specific miRNAs that play an oncogenic role in various cancers. FBXL19-AS1 causes cancers by acting in different signaling pathways ( Figure 6 ; Table 4 ) [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Molecular Mechanisms Of Fbxl19-as1mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver cancer is considered the sixth most frequent type of cancer, while hepatocellular carcinoma (HCC) is the most common type of liver cancer, consisting of 75-85% of all cases according to GLOBOCAN 2018 data (87,(99)(100)(101). Currently, serum AFP is the most widely used biomarker for HCC screening, despite its low sensitivity and a high false-negative rate for early HCC diagnosis.…”
Section: Liver Cancermentioning
confidence: 99%